An Ordinance to Prevent and Punish Certain Misdemeanors, §§ 1-4, General Ordinances of the Incorporated Village of Clifton (1874). - (:unkn) unknown (General Publisher, 1874)
Be it ordained by the Council of the Incorporated Village of Clifton, That it shall be unlawful, except for persons in military array, or to enforce the laws, or in defence of persons or property, to discharge any description of fire-arms within the corporate limits of the village. Also prohibited the killing of certain birds with a firearm.
--
Keywords: DISCHARGE; HUNTING REGULATION